(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The paper examines the alternative food networks in the agri-food sector in their variety of forms focusing on the issue of sustainable production and consumption, and particularly high quality and safety of products. Special attention is paid to the development of organic production and the potential to integrate it with some types of alternative food networks in Bulgaria. The study was implemented at the INVEST Regional Living Lab in Bulgaria under the research task of Alternative food chains and new business models. The focus on the development process of open innovations in the living lab predetermined the use of the participatory approach in the quadruple helix of research work. The opportunities of students’ involvement are of special consideration, particularly emphasizing the need of new training programs and approaches oriented towards the real business and practice for capacity building in sustainable rural development. The paper presents a business model for development of an alternative food network in Bulgaria considering the main characteristics of the spatial, social and economic proximity in short production and distribution chains. The model envisages students’ engagement in the main activities of an entrepreneurial initiative in University of agribusiness and rural development.